C3091418 - Hence AB x = A B x = A = It means that the...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
18. Let A and B be n × n matrices and let C = AB . Prove that if B is singular then C must be singular. Proof. Suppose that B is singular. By the part “(b) (a)” of Theorem 1.4.2, ( why this part? ) the equation B x = 0 has a nontrivial solution. That is, there is a vector x 0 6 = 0 such that B x 0 =
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: . Hence, AB x = A ( B x ) = A = . It means that the equation AB x = has a nontrivial solution x 6 = . By the part “(a) ⇒ (b)” of Theorem 1.4.2, ( again, why this part? ) C = AB is singular. / 1...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online